Un village congolais des environs de Loango - Révérend père Patron... (Wikimedia Commons, 1910)
Carte postale ancienne issue de Wikimedia Commons. Titre: Un village congolais des environs de Loango. A village with houses in vegetable materials, roofs with palm leaves and walls
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons